Open innovation in SMEs of developing and transitional economies - Rahman, Hakikur (2012)
Despite being accepted by corporate entrepreneurs and large business houses around the globe, the ad-aptation of strategies and concepts belonging to the newly evolved dimension of entrepreneurships, and the open innovation (OI), countries in the East, West or Southare yet to accommodate open innovation strategies in their business practices - especially in efforts to reach out to the grassroots communities. By far, firms belonging to the small- and medium-sized enterprises (SMEs), irrespective of their num-bers and contributions towards their national economies, are far behind in accepting open innovation strategies for their business developments. While talking about this newly emerged business dimension, it comprises of complex and dynamically developed concepts like management of intellectual property aspects, administration of patents and copyright issues, or supervision of market trend for minute details related to knowledge acquisition. All these issues are largely responsible for adding value to the busi-ness proposition in terms of economy or knowledge gain, and organizations or entities acting in this aspect deserve comprehensive investigation. As most of the developed countries have already adopted open innovation strategies, finding this as a weak link in terms of entrepreneurships in less developed countries, this chapter intends to seek answers related to the mentioned issues focusing adaption of open innovation strategies in developing and transitional economies. It is a longitudinal study on business houses or national efforts from countries belonging to these categories, deducting from a literature review. The chapter goes on looking into various aspects of business development incorporating OI concepts, synthesizes building a reasonable framework to be applicable in the target economies, points out to some future research aspects, and concludes the finding of this research. This study is supposed to enhance the knowledge of entrepreneurs and researchers by gaining specific knowledge on the trend of open innovation strategies in developing and transitional economies.